Seleção de descritores e divergência genética entre acessos de Fisális (Physalisangulata L.) - Silva, Hortência Kardec da (2018)
Physalis angulata L. is a species that has relevant interest because it presents pharmacological potential and produces fruits with high nutraceutical content. However, lack of information to support the rational exploration of physalis can lead to the loss of genetic resources of the species, making evident the need for a scientific involvement in research.The objective of the present work was to select important morphoagronomic descriptors for the characterization and evaluation of P. angulata germplasm, as well as to evaluate the genetic divergence between the accessions of the germplasm bank of the UEFS, by means of qualitative and quantitative traits. Twelve quantitative descriptors and 22 qualitative descriptors were analyzed in six accessions of camapu.Quantitative descriptor discarding was based on direct selection and Singh method, while qualitative descriptors were analyzed by entropy. The study of genetic divergence was performed for each dataset.From each of the dissimilarity matrices, the genetic divergence was evaluated using the Tocher optimization method and the hierarchical method of linkage between groups (UPGMA).Four common descriptors in direct selection and the Singh method were considered redundant.The list of minimum descriptors to describe physalis accesses was composed of 14 descriptors: plant height, stem diameter, north-south fruits, number of fruits per plant, length of leaf blade, length of cochlea, longitudinal length of fruit and length cross of the fruit, growth habit, stem color, leaf margin shape, immature chalice color, fruit shape and immature fruit color.The clustering analysis between the six accessions, using the method of average linkage between groups, based on the quantitative and qualitative characteristics and the joint analysis of the qualitative and quantitative variables, allowed the formation of two groups for each data set respectively. It was found that, although the final structure showed to be similar, between the methods of mean binding between groups and Tocher, changes in the constituent accesses of each group were observed when the two methods were compared.The discarding of four quantitative and 16 qualitative descriptors does not cause significant information losses and minimizes costs in the characterization of the germplasm of the species. There is genetic variability, for the quantitative and qualitative characters, in the group of accesses of P. angulata evaluated.